2017
DOI: 10.1155/2017/3978595
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Potential of Olfactory Ensheathing Cells and Mesenchymal Stem Cells in Spinal Cord Injuries

Abstract: Spinal cord injury (SCI) is a devastating neurological condition that affects individuals worldwide, significantly reducing quality of life, for both patients and their families. In recent years there has been a growing interest in cell therapy potential in the context of spinal cord injuries. The present review aims to discuss and compare the restorative approaches based on the current knowledge, available spinal cord restorative cell therapies, and use of selected cell types. However, treatment options for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Over the years, OEC transplantation has advanced to the forefront of therapeutic innovation for spinal cord repair 36 , 37 . Although they may be appropriate for the treatment of spinal cord injury, transplantation studies have reported variable findings.…”
Section: Oecs In Spinal Cord Repairmentioning
confidence: 99%
“…Over the years, OEC transplantation has advanced to the forefront of therapeutic innovation for spinal cord repair 36 , 37 . Although they may be appropriate for the treatment of spinal cord injury, transplantation studies have reported variable findings.…”
Section: Oecs In Spinal Cord Repairmentioning
confidence: 99%
“…Olfactory ensheathing cells (OECs) are specialized glial cells residing in both the PNS and CNS that share properties of both astrocytes and SCs. In animal SCI models, they have been shown to mediate regeneration and functional reconnection [104]. Functional gains in these models have also been reported [105].…”
Section: Olfactory Ensheathing Cellsmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are of mesodermal lineage found in bone marrow, cartilage, adipose tissue, placenta, umbilical cord, and the perivascular region of most organs that can differentiate into osteocytes, adipocytes, and chondrodytes [104]. They produce growth factors, neuroprotective cytokines, and chemokines, reduce inflammation, modulate glial scar formation, and mediate apoptosis [112].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…This attribute explains that enhancement of axonal extension after injury is possible and it can help neural regeneration, as a result of the expression of molecules implicated in that process ( Table 2) [2,59].…”
Section: Olfactory Ensheathing Cellsmentioning
confidence: 99%